The Non-ureogenic Stinging Catfish, Heteropneustes fossilis, Actively Excretes Ammonia With the Help of Na+/K+-ATPase When Exposed to Environmental Ammonia - Chew, Shit F.; Tan, Stephanie Z. L.; Ip, Sabrina C. Y.; Pang, Caryn Z.; Hiong, Kum C.; Ip, Yuen K. (Frontiers in Physiology, 2020)
The stinging catfish, Heteropneustes fossilis, can tolerate high concentrations of environmental ammonia. Previously, it was regarded as ureogenic, having a functional ornithine-urea cycle that could be up-regulated during ammonia-loading. However, contradictory results indicated that increased urea synthesis and switching to ureotelism could not explain its high ammonia tolerance. Hence, we re-examined the effects of exposure to 30 mmol l1 NH4Cl on its ammonia and urea excretion rates, and its tissue ammonia and urea concentrations. Our results confirm that H. fossilis did not increase urea excretion or accumulation during 6 days of ammonia exposure, and lacked detectable carbamoyl phosphate synthetase I or III activity in its liver. However, we discovered that it could actively excrete ammonia during exposure to 8 mmol l1 NH4Cl. As active ammonia excretion is known to involve Na+/K+-ATPase (Nka) indirectly in several ammonia-tolerant fishes, we also cloned various nkaα-subunit isoforms from the gills of H. fossilis, and determined the effects of ammonia exposure on their branchial transcripts levels and protein abundances. Results obtained revealed the presence of five nkaα-subunit isoforms, with nkaα1b having the highest transcript level. Exposure to 30 mmol l1 NH4Cl led to significant increases in the transcript levels of nkaα1b (on day 6) and nkaα1c1 (on day 1 and 3) as compared with the control. In addition, the protein abundances of Nkaα1c1, Nkaα1c2 and total NKAα increased significantly on day 6. Therefore, the high environmental ammonia tolerance of H. fossilis is attributable partly to its ability to actively excrete ammonia with the aid of Nka.